Enhancing Employee Performance: The Mediating Role of Organizational Commitment - Kurniawan, Iwan; Pramono, Suwito Eko; Yulianto, Arief; Formen, Ali (Universitas Negeri Semarang, 2024)
This study aims to examine the role of organizational commitment as a mediator in the relationship between work motivation, self-efficacy, and employee performance. The research focuses on all employees of the Central Java Regional Office of the Ministry of Law and Human Rights, with a sample of 189 respondents selected using Slovin's formula. Data was collected through a questionnaire featuring a 5-point agree-disagree scale, and analyzed using path regression analysis. The findings reveal a significant positive effect of work motivation and self-efficacy on organizational commitment. Moreover, work motivation and self-efficacy also impact employee performance. Organizational commitment effectively mediates the effect of work motivation and self-efficacy on employee performance with a total indirect effect. The Central Java Regional Office of the Ministry of Law and Human Rights should implement policies to boost organizational commitment among employees through various motivational strategies and efforts to enhance self-efficacy.